Biochemistry Free For All - Ahern, Kevin; Rajagopal, Indira; Tan, Taralyn (Open textbook library., 2018)
We are happy to welcome you to our second Open Educational Resource (OER) textbook, Biochemistry Free For All. Biochemistry is a relatively young science, but its rate of growth has been truly impressive. The rapid pace of discoveries, which shows no sign of slowing, is reflected in the steady increase in the size of biochemistry textbooks. Growing faster than the size of biochemistry books have been the skyrocketing costs of higher education and the even faster rising costs of college textbooks. These unfortunate realities have created a situation where the costs of going to college are beyond the means of increasing numbers of students.